2018
DOI: 10.1002/slct.201702831
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Coupling of Naphthols to Ketones: An Approach to 1,2‐Diketones

Abstract: 1,2‐Diketones are highly useful building blocks for the synthesis of pharmaceuticals, natural products and heterocycles. A simple and efficient route to 1,2‐diketones is developed here. The strategy involves coupling of naphthols to methyl ketones via oxidative C−H functionalization of methyl group of ketones. CuI (10 mol %) is used as catalyst and FeSO4.7H2O (10 mol %) as additive, both of which are environmentally benign and cheap. The reaction is carried out in DMSO solvent at 120 oC for 8–10 h. Little amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…7H 2 O (10 mol%) as additive (Scheme 22). [43] In this reaction, molecular oxygen was used as the oxidant and the reaction was carried out in DMSO at 120 °C. The authors have prepared a library of 1,2‐diketone 61 by using various substituted aryl methyl ketones 59 and 2‐naphthols 60 in moderate to good yields (55–74%).…”
Section: Synthesis Of 12‐diketones Starting From Ketonesmentioning
confidence: 99%
See 1 more Smart Citation
“…7H 2 O (10 mol%) as additive (Scheme 22). [43] In this reaction, molecular oxygen was used as the oxidant and the reaction was carried out in DMSO at 120 °C. The authors have prepared a library of 1,2‐diketone 61 by using various substituted aryl methyl ketones 59 and 2‐naphthols 60 in moderate to good yields (55–74%).…”
Section: Synthesis Of 12‐diketones Starting From Ketonesmentioning
confidence: 99%
“…7H 2 O (10 mol%) as additive (Scheme 22). [43] In this reaction, molecular oxygen was used as the oxidant and the reaction was carried out in DMSO at 120 °C. The authors have prepared a library of 1,2-diketone 61 by using various Cao and co-workers reported another interesting Cu(OAc) 2catalyzed regioselective dicarbonylation reaction for the synthesis of 1,2-diketones bearing animidazo[1,2-a]pyridine scaffold 65/66 involving the reaction between imidazo[1,2-a] pyridines 62 and acetone 63 or N,N-disubstituted acetamides 64 in the presence ofmolecular oxygen (Scheme 23).…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…There are several existing methods to prepare 1,2-diketones, and the topic has been recently reviewed . Nearly all methods to prepare 1,2-diketones exploit oxidative transformations on alkyne, alkene, , ketone, , or 1,3-diketone precursors . Due to often strong oxidative conditions ( e.g ., permanganate) used in 1,2-diketone synthesis, many functional groups are not tolerated and the reaction scope in some cases is restricted to diaryl-1,2-diketones.…”
mentioning
confidence: 99%
“…In addition, these compounds can be prepared via oxidative-coupling pathways. 79 The classical preparation of 1,2-diketones (benzils) is the direct oxidation of benzoin using two equivalents of copper acetate in an acetic acid/water mixture for 15 minutes under reflux conditions which furnished benzil in 90% isolated yield (Scheme 6). 80 Scheme 6: Classic synthesis of 1,2-diketones from benzoin oxidation Among the reported methods in literature, alkene oxidation remains a direct route towards benzils, as they are cheaper and more easily accessible than other precursors.…”
Section: Accessible Routes Toward the Preparation Of 12-diaryl Diketonesmentioning
confidence: 99%